2015
DOI: 10.1087/20150307
|View full text |Cite
|
Sign up to set email alerts
|

The ethical issues in instructions for authors of Chinese biomedical journals

Abstract: ABSTRACT229 Chinese‐language biomedical journals from A Guide to The Core Journals of China were investigated for their guidance on 14 ethical issues. The issues of authorship, duplicate submission, privacy and confidentiality, and integrity of the data were mentioned in more than 50% of the journals. Except for the issues of authorship and protection of animals in research, significant differences were found between Chinese Medical Association Publishing House (CMAPH) journals (n = 67) and non‐CMAPH journals … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 18 publications
0
1
0
1
Order By: Relevance
“…About two-third of medical editors did not follow the five publishing websites in this survey. In 2015, we reported on an investigation of the ethical guidelines in instructions for authors of Chinese biomedical journals and found that there was little guidance (Wu & Zou, 2015). This may be due to the focus of China's publishing authorities who put more emphasis on political issues, grammar, and typos, which make medical editors focus on these and less on ethical issues.…”
Section: Ghostwriter Survey Resultsmentioning
confidence: 99%
“…About two-third of medical editors did not follow the five publishing websites in this survey. In 2015, we reported on an investigation of the ethical guidelines in instructions for authors of Chinese biomedical journals and found that there was little guidance (Wu & Zou, 2015). This may be due to the focus of China's publishing authorities who put more emphasis on political issues, grammar, and typos, which make medical editors focus on these and less on ethical issues.…”
Section: Ghostwriter Survey Resultsmentioning
confidence: 99%
“…Sin embargo, no existen estudios que aborden la ética en este campo de forma integral, frente a lo que ocurre en el área biomédica (Bosch et al, 2012;Strech;Metz;Knüppel, 2014;Wu;Zou, 2015).…”
Section: Introductionunclassified